Movement Games, Relay Races And Application Paths - Means of Training in School Physical Education - Lucian, Rodica; Bitang, Viorel (Arena-Journal of Physical Activities, 2022)
Introduction: In order to achieve high efficiency, efficiency in preparing students for life, it is necessary to address the issue in terms of methods and techniques appropriate to achieving the objectives, assessment methods (attractive and interesting), the efficiency of the use of devices and materials. Purpose: Using in the experiment described in the paper permanently motion games, relay races, application paths, I wanted to check their effectiveness and confirm the hypothesis that the method I chose to improve the manifestation of motor skills and level of motor skills is higher compared to two tests, and the methods used were correctly chosen and applied. Methodology: I highlighted the means of school physical education provided in the training program, and in them I presented aspects specific to the three means targeted in the experiment: movement games, relay races and application paths, which we also described in detail, also visually, through kinograms. I considered a special aspect, the one related to the cooperation between teachers and students in the school training process, without which the physical education lesson cannot achieve its objectives . Results: The results materialized in the level of preparation of the students and the progress registered in the experiment period show that, through the use of complex exercises, the activation of the students on the basis of awareness was achieved and their motor and spiritual forces were mobilized. Conclusion: the hypothesis I started from was that by systematically using the chosen means, they will make progress in the tests administered in the experiment.